Resolution of serologic problems due to cold agglutinin mediated autoimmune hemolytic anemia and its transfusion decision. Issue 8 (3rd July 2021) - Ying, Qiming; Lv, Dingfeng; Fu, Xiaomei; Shi, Shuanglu; Chen, Luyan; He, Yiwen; Yang, Jing; Yang, Shujun; Mu, Qitian
Abstract: Background: Autoimmune hemolytic anemia (AIHA) is a rare disease characterized by hemolysis caused by autoantibodies against erythrocyte surface antigen. These antibodies can be classified as warm, cold, or mixed types. Methods: We report two cases of cold agglutinin disease (CAD), which were eventually diagnosed owing to blood group discrepancy. Resolution was achieved after washing the red blood cells (RBCs) with warm saline and absorbing the autoantibodies at 4°C with the washed RBCs. We also assessed the patient's condition and discussed the strategy of blood transfusion. Results: The first case occurred after postoperative chemotherapy for rectal cancer, and the other manifested with anemia from the outset. Direct antiglobulin tests were positive and revealed autoantibodies against C3d only. Cold agglutinin titration was performed, and the titers of both were 1:1024. Eventually, the patient's condition stabilized without blood transfusion. Conclusion: The serological discrepancies observed in the blood transfusion department can successfully guide blood transfusion decisions in cases of CAD. Abstract : Many studies have investigated the diagnosis and treatment of CAS and CAD. They are usually diagnosed by clinicians and use blood transfusions to improve anemia. Transfusion physicians usually play a small role. Although at present, the laboratory has mastered the common treatment methods for patients with CAD, how to accurately evaluate CAD through sample properties, clinical signs, and laboratory test results has not been reported in detail. We aim to provide clinical guidance to avoid unnecessary blood transfusions and improve the hemoglobin level of patients through medical management. In our two cases, the serological discrepancies observed in the blood transfusion department successfully guide blood transfusion decisions in CAD and CAS, and both patients' hemoglobin levels gradually increased (Figure B‐C), without blood transfusion.